2013
DOI: 10.1371/journal.pone.0081839
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-30e* Regulation of Bmi1 Expression Mediated by Tumor-Associated Macrophages in Gastrointestinal Cancer

Abstract: Bmi1 is overexpressed in a variety of human cancers including gastrointestinal cancer. The high expression level of Bmi1 protein is associated with poor prognosis of gastrointestinal cancer patients. On the other hand, tumor-associated macrophages (TAMs) contribute to tumor growth, invasion, and metastasis by producing various mediators in the tumor microenvironment. The aim of this study was to investigate TAM-mediated regulation of Bmi1 expression in gastrointestinal cancer. The relationship between TAMs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…The average intensity of positively stained cells was given an intensity score from 0 to 3: 0, absent; 1, weak; 2, moderate; and 3, strong expression). The two scores were multiplied to characterize 15-PGDH expression as low (0-7) or high (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). CD163-positive cells were counted in four randomly selected area of a high-power field (9200) of a microscope.…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The average intensity of positively stained cells was given an intensity score from 0 to 3: 0, absent; 1, weak; 2, moderate; and 3, strong expression). The two scores were multiplied to characterize 15-PGDH expression as low (0-7) or high (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). CD163-positive cells were counted in four randomly selected area of a high-power field (9200) of a microscope.…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%
“…8,9 Solid tumors are composed of cancer cells and diverse types of stromal cells, including cancer-associated fibroblasts and TAMs. [10][11][12][13] Thus, tumor progression depends on not only the aggressive characteristics of cancer cells themselves but also on their interactions with stromal cells. A previous study reported that prostaglandin signal activation caused by TAMs promoted tumor metastasis.…”
mentioning
confidence: 99%
“…HT-29, HCT116 and SW620 colon cells were plated at 10 4 cells/well in a 96-well plate that contained 100 µl RPMI-1640 supplement with 10% fBS for 24 h (19). Then, the culture medium was replaced by PLD4-siRNA (20 nM) group, control-group cell supernatant of M1 macrophages for another 24 h. For cell proliferation assay, the cells were quantified using a Cell Counting kit-8 (CCK-8; Nanjing KeyGen Biotech, Co., Ltd., Nanjing, China).…”
Section: Cell Proliferation Assay Cell Cycle Assay and Apoptotic Cellsmentioning
confidence: 99%
“…During cancer progression, molecular changes arise in the tumor as well as in the neighbouring tissue stroma, with substantial experimental evidence indicating that the stroma contributes significantly to cancer progression (124) (130,131). In another study, collagen remodeling was associated with suppression of M a n u s c r i p t the tumor-suppressive let-7 miRNA in pancreatic ductal adenocarcinomas (132).…”
Section: Micrornas In the Cross-talk Between Cancer (Stem) Cells And mentioning
confidence: 99%